2018
DOI: 10.1039/c8ee01065j
|View full text |Cite
|
Sign up to set email alerts
|

Rapid route to efficient, scalable, and robust perovskite photovoltaics in air

Abstract: RSPP is a unique up-scalable method to produce high quality photoactive perovskite in seconds in open-air.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
35
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 36 publications
1
35
0
Order By: Relevance
“…Atmospheric plasma deposition is a thin‐film deposition technique, which provides a means for synthesizing metal oxide materials at low temperature and on plastic substrates . Molecular dissociation or fragmentation of a precursor can proceed via several nonhydrolytic reaction pathways, including thermal decomposition, photolysis, penning ionization, or oxidation by reactive oxygen and nitrogen species (RONS) . The fragmentation of the precursor creates a broad distribution of inorganic and organic radicals which undergo rapid step‐growth polymerization on the surface of a substrate .…”
Section: Introductionsupporting
confidence: 90%
“…Atmospheric plasma deposition is a thin‐film deposition technique, which provides a means for synthesizing metal oxide materials at low temperature and on plastic substrates . Molecular dissociation or fragmentation of a precursor can proceed via several nonhydrolytic reaction pathways, including thermal decomposition, photolysis, penning ionization, or oxidation by reactive oxygen and nitrogen species (RONS) . The fragmentation of the precursor creates a broad distribution of inorganic and organic radicals which undergo rapid step‐growth polymerization on the surface of a substrate .…”
Section: Introductionsupporting
confidence: 90%
“…We have demonstrated that open-air plasmas are effective at converting high-quality single, double, and triple cation compositions with a range of bandgaps into high-quality perovskite films (Hilt et al, 2018;Hovish et al, 2020;Rolston et al, 2020) and dense organosilicate barrier films (Rolston et al, 2017). This patented open-air Rapid Spray Plasma Process (RSPP) is a new scalable method for the ultra-fast deposition and cure of both efficient and mechanically robust thin films (Figures 1B,C) and PV modules (Figures 1D,E).…”
Section: Introductionmentioning
confidence: 99%
“…The application of plasma is mostly confined to surface cleaning and removal of impurities from fluorine doped tin oxide (FTO) and indium tin oxide (ITO) in dye-sensitized solar cells (DSSCs) and PSCs, improving device performance. However, recently the applications of plasma in PSCs have been widened to encompass improvement in device stability [51], surface modification [52], spray deposition of the perovskite active layer [53] and tuning the work function and surface energy of HTMs [54].…”
Section: Introductionmentioning
confidence: 99%
“…(iii) A scalable, atmospheric pressure plasma, post-deposition technique to rapidly form an efficient and mechanically robust CH3NH3PbI3 perovskite layer without the need of a hot plate for curing the active material was reported by Hilt et al [53]. An air plasma arc discharge was used for 250 ms exposure to obtain defect-free films showing ultrafast crystallization and a power conversion efficiency (PCE) of 15.7%.…”
Section: Introductionmentioning
confidence: 99%